DIETARY MANNAN-OLIGOSACCHARIDE INCREASES REACTIVE OXIGEN SPECIES PRODUCTION BUT DECREASES SERUM LYSOZYME IN HIGH LEVELS OF INCLUSION FOR NILE TILAPIA - Nycolas LEVY-PEREIRA; Ricardo Luiz Moro de SOUSA; Roberson SAKABE; Fernanda de Alexandre SEBASTIÃO; Elisabeth Criscuolo URBINATI; Fabiana PILARSKI (Boletim do Instituto de Pesca)
In the present experiment, the effects of mannan-oligosaccharide (MOS) on health and growth of Nile tilapia juveniles were investigated. In addition to the control treatment (without MOS),three levels of MOS were included in Nile tilapia diets (1, 8, and 15 g kgâË†"™1), and hematology, reactive oxygen species (ROS) production, lysozyme and productive parameters were analyzed. Fish blood was sampled at day zero (basal sample) and after 60 days of trial, and the productive parameters were evaluated at the end of the experiment. MOS feeding decreased the feed consumption (p = 0.0299) in fish fed with 1 and 8 g kg-1, but without any alteration in weight gain (WG) and feed conversion ratio (FCR). No changes were observed in the hematology due to MOS feeding after 60 days. However, the prebiotic caused changes in the innate immunity of fish, giving rise to ROS production in fish fed with 1 g kg-1 (p<0.0001) and decreasing the serum lysozyme activity of fish fed with 15 g kg-1 (p<0.0001). In conclusion, the authors recommend the inclusion of 1 g kg-1 for Nile tilapia juveniles feeding due to the positive effect in innate immune system.